SETS (Science Environment Technology and Society) Based Learning Implementation in Junior High School - Ardian Puguh Setia Budi; Widha Sunarno; S Sugiyarto (Pancaran Pendidikan, 2017)
Science, Environment, Technology and Society (SETS) based learning need to be developed in junior high school, because it can improve student's critical thinking skills. This study aimed to analyze the learning process in National Junior High School 2 of Jatisrono to implement SETS based learning. This study design was descriptive qualitative. Data were analyzed used Miiles&Huberman by observation, deepth interviews, and questionnaires. This study focused on the learning process, learning materials, as well as the results achieved by students cognitive abilities in the learning process. The results showed that the learning was done in National Junior High School 2 of Jatisrono not used SETS process-based learning. This is because teachers do not have a guide to innovate learning approaches, students are less interested in science learning and caused low cognitive abilities results.